2019
DOI: 10.1021/acs.langmuir.9b02848
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Ionic Transport Properties of Nanocomposite Electrolytes Based on Protic Ionic Liquids and Silica Nanoparticles

Abstract: In this study, the effect of hydrophilic silica nanoparticle (AEROSIL 200) addition on the rheological and transport properties of several protic ionic liquids (PILs) consisting of protonated 1,8-diazabicyclo[5.4.0]undec-7-ene cation (DBU) was studied. Interactions between the surface silanol groups of the silica nanoparticles and the ions of these PILs affected the nature of particle aggregation and the hydrogen bonding environment, which was reflected in the nonlinear rheological behaviors and transport prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…In a recent study on PIL-silica composites, we found a significant increase in the conductivity of the shear thickening composites of the methanesulfonate salt of protonated 1,8-diazabicyclo [5.4.0]undec-7-ene ([DBU][MSA]) and the silica particles within a certain composition range. 18 Strong hydrogen bonding was assumed between the silica surface and the ions to contribute toward an increase in the charge carrier density and efficient ionic correlations, thereby leading to conductivity enhancement. The absence of the notable conductivity enhancement in the MLS-silica composites suggests that the interaction of the silica surface with [BF 4 ] anion does not significantly alter the ionic environment in an effective way to enhance the charge carrier concentration or correlations of ionic motions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on PIL-silica composites, we found a significant increase in the conductivity of the shear thickening composites of the methanesulfonate salt of protonated 1,8-diazabicyclo [5.4.0]undec-7-ene ([DBU][MSA]) and the silica particles within a certain composition range. 18 Strong hydrogen bonding was assumed between the silica surface and the ions to contribute toward an increase in the charge carrier density and efficient ionic correlations, thereby leading to conductivity enhancement. The absence of the notable conductivity enhancement in the MLS-silica composites suggests that the interaction of the silica surface with [BF 4 ] anion does not significantly alter the ionic environment in an effective way to enhance the charge carrier concentration or correlations of ionic motions.…”
Section: Resultsmentioning
confidence: 99%
“…The two distinct rheological responses of the IL-silica nanocomposites were tuned via simple variations in the ionic structure of the ILs. [15][16][17][18] These IL-nanoparticles hybrid systems with unique colloidal stabilization behavior and remarkable rheological properties have shown potential in diverse applications, such as catalysis, separation technology, shock resistive materials, electrochemical sensors and electrolytes. 19,20 As Li ion conducting liquid electrolytes, MLSs were found to be superior to AIL-Li salt binary electrolytes in terms of Li ion conductivity and charge-discharge rate capability of Li/LiCoO 2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…If this model remained valid in ionic liquids, they could not be "good" dispersing media of colloids because they are considered as extremely concentrated electrolyte solutions. However, stable dispersions of nanoparticles have been obtained in various ionic liquids, [11][12][13][14][15][16][17][18][19][20][21][22][23] implying a different stabilization mechanism but electrostatic repulsion. The role of the formation of solvation layers of ions at the surface of the nanoparticles, acting as protective layers, is one possible explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the isotropic particles are the focal point in the design and synthesis of high performance ionogels, such as silica (SiO 2 ), titanium dioxide (TiO 2 ), nanodiamonds, and zirconium dioxide (ZrO 2 ) . While for the ionogel electrolytes based on anisotropic nanoparticles, the existing literature has been focused mainly on carbon nanotubes (CNTs) and graphene oxide (GO) .…”
Section: Introductionmentioning
confidence: 99%